ANALISIS KINERJA KEUANGAN PADA PERUSAHAAN GO PUBLIC SUB SEKTOR PERTAMBANGAN BATUBARA DI BURSA EFEK INDONESIA (BEI) - Rahmi Aryanti; Junaidi, Junaidi (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2020)
This study aims to determine the financial performance of coal mining companies that have gone public and listed on the Indonesia Stock Exchange (BEI) from 2008 to 2012. By using 13 samples of coal mining companies, financial data are analyzed using financial ratios and Du Pont analysis approach. Furthermore, different test performed on average every financial ratios. The research proves that the overall financial performance of a coal mining company shows unsatisfactory results (bad). And the numbers generated financial ratios of each company generally does not show significantly different results with each other.